Immigration-trade links : the impact of recent immigration on portuguese trade - Faustino, Horácio C. (2010)
This study analyzes Portuguese immigration during the period 1995-2006 and estimates the effects of an increase in the stock of immigrants and of the increased percentage of highly-skilled immigrants employed in manufacturing industry. Furthermore, the effects are estimated of immigrant entrepreneurs active in manufacturing industry on Portugal’s bilateral trade with 38 countries. The latter group includes, in addition to the member-countries of the EU27, five African countries with Portuguese as their official language, and known as PALOPs. In 2006, these two blocs combined accounted for 83% of Portugal’s trade in goods and 89% of its immigrant stock. Panel data is used to conduct an econometric analysis. The study finds that a 10% increase in the immigrant stock will produce the following effects on Portugal’s bilateral trade with these countries: an increase of 2.8% in exports, an increase of 2.66% in imports, an increase of 1.87% in IIT, an increase of 4.01% in HIIT and an increase of 1.48% in VIIT. In addition, we conclude that higher percentages both of highly skilled immigrant workers and immigrant employers in manufacturing industry have a positive effect on exports, IIT and VIIT.